الإجراءات الشكلية لإعداد الاتفاقيات الجماعية للعمل في التشريع الجزائري والتشريعات المقارنة (Al-Mostansiriyah journal for Arab and international studies, 2026)
Abstract: The collective agreement, as an effective tool for regulating the labor relationship and achieving social peace, is of particular importance In order to confirm the content of the collective agreement, as well as to prevent any disputes that may arise regarding it, and to announce this content to others in order to facilitate their joining it, the Algerian legislator required, in Article 114 of Law 90-11, the necessity of having a writing element for the validity of concluding the agreement.It also stipulated the necessity of announcing it, which is also stipulated.In Article 126 of the same law.Keywords: collective agreement, writing, advertising, formalities.